NON-DESTRUCTIVE METHOD FOR QUALITY CONTROL ASPHALT CONCRETE PAVEMENT - , В. И., Н. А., И. Е., А. А. (Municipal economy of cities (Technical science), 2013)
The method of non-destructive quality control of asphalt concrete by hardness were proposed. The effect of the weight drop height and its weight on the hardness using the dynamic hardness testerwere investigated. The optimal values of the varied parameters of hardness were defined.